Impact of Internet Use on Multi-dimensional Health: An Empirical Study Based on CGSS 2017 Data - Han, Junhui; Zhao, Xiaoqiong (Frontiers in Public Health, 2021)
Based on the data of the Chinese General Social Survey (CGSS) in 2017, the paper divides overall health into physical, mental, and social health, using the ordered probit model to examine the impact of Internet use on multi-dimensional health. It then discusses the possible heterogeneity in different groups and underlying mechanism. Results found that using the Internet can improve the health level in multiple dimensions. After endogenous and robustness tests, the results remain robust. Heterogeneity analysis shows that Internet use has more obvious effects on the health of senior high school education or above, the elderly, and men. Further analysis of the mediating effect model found that information, leisure, and social preferences are important path mechanisms for Internet use to promote physical, mental, and social health, respectively.